1958
DOI: 10.1172/jci103721
|View full text |Cite
|
Sign up to set email alerts
|

Application of Continuous Flow Electrophoresis to the Study of the Blood Coagulation Proteins and the Fibrinolytic Enzyme System. I. Normal Human Materials1

Abstract: Continuous flow filter paper electrophoresis, as developed by Svensson and Brattsen (1), Grassmann and Hannig (2-4) and Durrum (5), offers a method of plasma fractionation in which protein denaturation appears minimal. This study involves the testing of such fractions for biological activity in various coagulation systems. With the exception of fibrinogen, the coagulation proteins are present in plasma in minute amounts which, at the present time, can be assayed only by their activities in specific clotting sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1959
1959
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…The patient's plasma and a normal plasma were fractionated by starch block electrophoresis (23 (20,21). The initial 10 ml of plasma was separated into 28 fractions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient's plasma and a normal plasma were fractionated by starch block electrophoresis (23 (20,21). The initial 10 ml of plasma was separated into 28 fractions.…”
Section: Resultsmentioning
confidence: 99%
“…The test was then continued for an additional 6 minutes. E) To determine the inhibitory effect of isolated fractions, the patient's plasma was fractionated into 28 fractions by the continuous flow electrophoresis method of Lewis, Walters, Didisheim, and Merchant (20,21). For testing, a single normal donor served as the tontrol, and the same hemophiliac plasma was used throughout.…”
Section: Methodsmentioning
confidence: 99%
“…However, a profusion of experiments, beginning with those of Bordet and Gengou (33), demonstrated that glass and certain other substances can initiate or accelerate clotting in plasma depleted of its cells. One site of action of glass is Hageman factor, present in normal plasma lbut lacking in the plasma of patients with Hageman trait (2)(3)(4)(5)(6)(7)(8). Perhaps other factors are altered as well (7,34); it is difficult to distinguish between a direct effect of glass upon a clotting factor and an indirect effect mediated through its activation of Hageman factor.…”
Section: Discussionmentioning
confidence: 99%
“…The methods have been described previously (1,2). Plasmas were obtained from six patients, five of whom had suffered from severe and one (C.F.)…”
Section: Methodsmentioning
confidence: 99%
“…A previous communication (1) concerned the application of continuous flow electrophoresis to the fractionation of normal blood preparations and the study of the coagulation proteins in these fractions. It was considered of some interest to apply the same techniques to pathological plasmas obtained from patients suffering from congenital deficiencies of AHF (antihemophilic factor A) and PTC (plasma thromboplastin component, Christmas factor, antihemophilic factor B).…”
mentioning
confidence: 99%